Pembuatan Website Katalog Produk Kuliner Sebagai Media Promosi dan Pemasaran UMKM Sate Ayam Ponorogo Pak Ici - Febriyanti, Choirun Nisa'; Puspita, Della; Badruzzaman, Mohammad Ryan; Fatar, Mohammad Firdaus Al; Ruba’, Muhammad Gusnanda (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The service team took the initiative to create a product catalog website with the strategic aim of strengthening and developing small and medium-scale culinary businesses (MSMEs). This website was designed with the intention of expanding market reach and increasing sales of Ponorogo Pak Ici Chicken Satay products. With an attractive layout, the website presents comprehensive information about products, including images, descriptions, prices, and easy-to-reach contacts. Additional features such as location maps, customer testimonials, and online order forms are also provided. It is hoped that the creation of this website can make a positive contribution to the growth of Ponorogo Pak Ici Chicken Satay MSMEs and support the promotion of local culinary delights. The methods used include identifying website objectives, such as increasing sales and expanding market share, as well as designing a visual appearance that is in accordance with the MSME brand identity. As a result, the website succeeded in expanding product knowledge, increasing sales, and providing accurate information to attract consumer interest. Overall, the creation of this website was successful in increasing online visibility, enabling customers to discover products, and reducing promotional costs.